(untitled) (Research, Society and Development, 2020)
Education constituted itself as a privilege of the few, becoming a fundamental right in the 1988 Constitution. In the prison context, only from 2011 it became a right to re-sentence, after many years of processing the bill in the National Congress. Data from the survey of penitentiary information reveal that more than half, that is, 60.38% of the prison population has low schooling and only 10.58% are enrolled in some educational activity. Therefore, the aim of this study was to promote a theoretical reflection on the right to education in the Brazilian prison system, for this purpose made use with bibliographic review and consulted the main norms that deal with education in the prison environment. Thus, it was possible to correlate that, despite recent normative advances, the supply and access to education in prison faces many challenges, including the way it has been developed, being related to the political wills of each government; and, also, the understanding of society and prison managers who see education as a privilege opposing a right that is independent of the condition of deprivation of liberty.